Vitamin D supplementation is beneficial in improving the prognosis of patients with acute respiratory failure in the intensive care unit: a retrospective study based on the MIMIC-IV database - Hu, Song; He, Qian; Xie, Jun; Liu, Hui; Zhou, Rong; Li, Chong (Frontiers in Medicine, 2023)
Background: Vitamin D plays a critical role in the regulation of multiple physiological pathways. Vitamin D deficiency may be a risk factor for life-threatening clinical conditions. Several studies have found that vitamin D supplementation in critically ill patients improves prognosis. The purpose of this study was to determine the association between vitamin D and the prognosis of patients with acute respiratory failure (ARF). Methods: In this retrospective cohort study, we collected clinical information of ARF patients from the Medical Information Mart for Intensive Care IV (MIMIC-IV) version 2.0 database. The outcome of this study was in-hospital mortality, intensive care unit (ICU) mortality. Patients were divided into the no-vitamin D and vitamin D groups according to whether they received supplementation or not. The correlation between vitamin D and outcome was examined using Kaplan-Meier (KM) survival curves, Cox proportional risk regression models and subgroup analyses.Propensity-score matching (PSM) was used to ensure the robustness of our findings.The study finally included 7994 patients with ARF, comprising 6926 and 1068 in the no-vitamin D and vitamin D groups, respectively. The Kaplan-Meier survival curve indicated a significant difference in survival probability between the two groups. After adjustment for a series of confounders, the multivariate Cox proportional hazards models showed that the hazard ratio (95% confidence interval) values for in-hospital and ICU mortality in the no-vitamin D group were 1.67(1.45,1.93) and 1.64(1.36,1.98), respectively. The results of propensity score-matched (PSM) analysis were consistent with the original population. In the subgroup analysis, Vitamin D supplementation was associated with lower in-hospital mortality in patients with higher clinical scores (SOFA score>=8, OASIS>=38).Our study concluded that Vitamin D supplementation may reduce in-hospital and ICU mortality in patients with ARF in the ICU. There may be a beneficial effect on in-hospital mortality in patients with higher clinical scores.Additional randomized controlled trials are needed to follow up to confirm the relationship between vitamin D supplementation and ARF.